3D printed chitosan scaffolds: A new TiO2 support for the photocatalytic degradation of amoxicillin in water. (15th October 2019) - Bergamonti, Laura; Bergonzi, Carlo; Graiff, Claudia; Lottici, Pier Paolo; Bettini, Ruggero; Elviri, Lisa
Abstract: TiO2 -supported chitosan scaffolds (TiO2 /CS) are here proposed as promising material for wastewater treatment, in particular for the removal of pharmaceutical compounds. TiO2 /CS are tested for the amoxicillin photodegradation under UV/Vis irradiation. Amoxicillin (AMX) is an antibiotic of the beta-lactam family. Due to the release of antibiotics in wastewater and their persistence in the environment, harmful effects can develop on the aquatic and terrestrial organisms. TiO2 chitosan scaffolds with photocatalytic activity for wastewater remediation have been prepared by 3D printing using commercial P25-TiO2 . The formulation for the 3D printer was prepared by dispersion of chitosan and TiO2 in powder form at the concentration 6% w/v and 1% w/v, respectively. The TiO2 particles (crystalline anatase and rutile phases) embedded in the chitosan have a size of about 20 nm, like in the starting material, as verified by X-ray diffraction and Raman spectroscopy and are homogeneously distributed in the scaffold, also after repeated photocatalytic tests, as revealed by SEM-EDS. The mechanical properties of the 3D structures are suitable for the targeted application as they can be easily handled without breakage. The AMX photodegradation efficiency under light irradiation by TiO2 /CS made with scaffolds of different thicknesses (3, 5, 15 layers), was assessed in water by means of UV–Vis absorption and HPLC/UV measurements, at two different AMX:TiO2 molar ratios: 1/100 and 1/10. The 3D printed TiO2 /CS system, even after repeated cycles, shows a high photodegradation efficiency, compared to the direct AMX photolysis. A zero-order kinetics for TiO2 supported photodegradation was found, whereas a pseudo-first order was observed for water dispersed TiO2 . Mass spectrometry analysis revealed the presence of AMX degradates such as penilloic and penicilloic acids and diketopiperazine. The proposed 3D printed chitosan scaffolds may be used as reusable substrate for the TiO2 photocatalytic degradation of antibiotic pollutants in wastewater. Graphical abstract: Image 1 Highlights: TiO2 -supported chitosan scaffolds are proposed for photocatalytic wastewater treatment. Environmentally friendly chitosan scaffolds are designed by 3D printing. The scaffolds are reusable for water purification from pollutants. Amoxicillin in water has been degradated by embedded TiO2 with high efficiency.